2010
DOI: 10.2478/v10086-010-0013-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and antioxidant defense system in spawn of brown trout (Salmo trutta m. trutta L.) affected by ulcerative dermal necrosis

Abstract: Abstract. The objective of the present study was to investigate the importance of the antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), and glutathione peroxidase (GPX) in the defense against lipid and protein oxidation in spawn from female brown trout, Salmo trutta m. trutta L. affected by ulcerative dermal necrosis (UDN). UDN induced increased lipid and protein oxidation levels. The current results show that UDN infection led to oxidative stress with the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…Our results suggest, for the first time, that oxidative stress in the liver of sea trout may be induced by UDN syndrome. Moreover, these results complete the previous study of our laboratory reporting an inhibition of antioxidant defense system and cumulation of oxidative stress biomarkers in the liver, heart and muscle of sea trout with UDN syndrome (Kurhalyuk et al, 2009(Kurhalyuk et al, , 2010Tkachenko et al, 2011).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results suggest, for the first time, that oxidative stress in the liver of sea trout may be induced by UDN syndrome. Moreover, these results complete the previous study of our laboratory reporting an inhibition of antioxidant defense system and cumulation of oxidative stress biomarkers in the liver, heart and muscle of sea trout with UDN syndrome (Kurhalyuk et al, 2009(Kurhalyuk et al, , 2010Tkachenko et al, 2011).…”
Section: Discussionsupporting
confidence: 73%
“…The depletion of antioxidant defense system and the changes in the activities of various antioxidant enzymes indicative of lipid and protein oxidation have been implicated in oxidative tissue damage (Limón-Pacheco and Gonsebatt, 2009). Our previously studies have shown that UDN syndrome seems to be quite capable to cause of oxidative stress in liver, muscle, heart, and spawn of brown trout (Kurhalyuk et al, 2009(Kurhalyuk et al, , 2010Tkachenko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation assessed as TBARS, increased in most tissues of UDN-positive trout (Kurhalyuk et al 2009(Kurhalyuk et al , 2010. The present study showed that TBARS level in the erythrocytes of UDN-positive females was higher compared to control group (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Our previous studies on pro-and antioxidative processes have revealed that some relationships have been found between oxidative stress markers and antioxidant enzyme activities in tissues of UDN-positive trout (Kurhalyuk et al 2009(Kurhalyuk et al , 2010. This study was aimed to check whether there are general patterns of relationships between oxidative stress indices in trout affected by UDN syndrome and physiological response of their erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation